The Role Of Mediation Based On Regulation Of The Minister Of Agrarian And Spatial Planning/Head Of The National Land Agency Number 21 Of 2020 Concerning The Handling And Settlement Of Land Cases - Yusri, Muhamad; Moonti, Roy Marthen; Ahmad, Ibrahim; Kasim, Muslim (International Journal of Law, Crime and Justice, 2024)
Settlement of land cases through mediation carried out by the Land Office of Boalemo Regency refers to Regulation of Agrarian Affairs Minister and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning Handling and Settlement of Land Cases. Mediation as an alternative for resolving land cases, it is necessary to popularize "mediator". A mediator must know psychologically the condition of the parties, so that they feel comfortable and the problem is resolved comfortably. In addition, the mediator must have analytical skills and expertise in creating a personal approach for the parties involved in the dispute. The mediator must be able to understand and give a positive reaction to the perceptions of each party. The goal is to build good relationships and trust. The parties' trust in the mediator makes it easier to reach a consensus. The priority regarding the purpose and function of the mediator is to resolve land cases in order to resolve cases without creating new ones. The research method that the author uses in this study is the empirical juridical law method, empirical juridical law is a study in addition to looking at the positive legal aspects, it also looks at its application or practice in the field. Thus the empirical juridical approach is a legal research method that seeks to see the law in a real sense or it can be said to see, examine, how the law works in society. The results shows that the handling and settlement of land cases through mediation at the Land Office of Boalemo Regency Land Office is done and carried out based on the Agrarian Affairs Minister Regulation and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning Handling and Settlement of Land Cases. Constraints faced in handling and resolving land cases through mediation at the Land Office of Boalemo Regency are in the form of juridical and non-juridical constraints. The juridical constraint is the technical instructions for the mediation procedure referred to by the regulation have not yet been published, while the non-juridical constraint is in the form of limited qualified human resources as mediators. Based on this, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency in the future must make structured, systematic and massive improvements to the mediation process by immediately issuing technical instructions and improving the quality of human resources in terms of being a mediator through guidance, training and direction.